A csehszlovák-magyar lakosságcsere hatása Csanád vármegye oktatási életére - M. Pelesz, Nelli (Közép-Európai Közlemények, 2009)
The gentitial consistency of the three villages in Csanád county (now the part of Csongrád county), populated by slovakians (Pitvaros, Csanádalberti és Ambrózfalva), was changed between 1945 and 1948. The human and economic casiulties of the World War II created difficult situation to the public education in Csanád county. The number of slovakian students fallen after 1946. The author used the documents of Csongrád Megyei Levél-tár (Archives of Csongrád County), the reports of local school-inspector.